Pemberdayaan Taman Pendidikan Al-Quran (TPA) Sebagai Pusat Pendidikan Karakter Religus (Pengabdian di TPQ Silastra Condong Catur,TPQ Darul Falah Maguwo Harjo Maguwo Harjo, TPA Al-Huda Caturtunggal,Yogyakarta) - Yayuk Hidayah; Suyitno Suyitno; Lisa Retnasari (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2019)
The service partner is the TPQ Silastra Condong Catur, Darul Falah TPQ Maguwo Harjo Maguwo Harjo, TPA Al-Huda Caturtunggal, Yogyakarta. The reason for determining the proposed object problem is the background of the problems that arise in the lack of use of the Al-Quran Education Park (TPA) as the center of religus character education. The solution proposed by the dedication team was to integrate the Al-Quran reading and writing learning with the values of religious characters to the santri. The method used by the service team is consultation, mentoring, and training. The contribution proposed by the dedication team is for TPA to maximize the role of TPA in religious character education. For santri, they can get additional knowledge. For the community, they can support the efforts to cultivate religious character education. The conclusion is that the existence of TPA is still essential in society as a place of education for children.